Divinely Prescribed Evil and Moral Knowledge in Islam and Beyond - Akhlaghi, Farbod (AGATHEOS – European Journal for Philosophy of Religion, 2025)
Can one who takes Scripture to be the word of God, and who takes their independent moral judgements to be reliable, reconcile such beliefs with Scriptural injunctions that appear to permit and require evil actions? That is the Problem of Divinely Prescribed Evil. An ethics-first solution takes our independent moral judgements to be reliable and attempts to reconcile them with seemingly divinely prescribed evil. Amir Saemi (2024) offers a prima facie promising ethics-first solution: take Scriptural injunctions to be not moral, but legal. In this paper, I critically examine this proposal. After raising worries about Saemi’s argument for his solution, I explore his analogy with the ethics and laws of war, raise three concerns for his solution, and present a dilemma which is, ultimately, an argument against Saemi’s solution. I end with some suggestions for further inquiry into this recalcitrant problem, and analytic philosophy of religion about Islam.